Effect of individual tree shelters on early survival and growth of a Quercus faginea plantation - Fabião, António (2009)
An experiment consistig of 4 plots planted with Quercus faginea seedlings with and without individual tree shelters was established at Serra de Sintra, 25 km to the North of Lisbon, to evaluate the influence of those shelters on growth and survival of this species at the early growth stage. The experimental design consisted of a treatment with shelters and a control, with two replicates, in a completely randomized experiment. Tree survival and growth were periodically monitored during 3 years and tree biomass was assessed at the end of the first and second years.